Analysis of Facilities And Infrastructure Management In Supporting Student Learning Outcomes At SMPN 1 Mesuji Ogan Komering Ilir - AlHaq, Abu Bakar Sidiq; Martha, Alfroki; Fitria, Happy (Jurnal Pendidikan Tambusai, 2021)
This study aims to analyze the management of facilities and infrastructure to support student learning outcomes at SMP Negeri 1 Mesuji Ogan Komering Ilir. This study uses a qualitative method. The research subjects were principals, vice principals in the field of facilities and infrastructure, teachers and students. Retrieval of data using interview techniques, documentation and observation. The results of this analysis include several components, including the planning of facilities and infrastructure, organizing facilities and infrastructure, implementing management and controlling of facilities and infrastructure. This analysis of constraints and solutions at school is related to cost or funding problems and is related to students